Ethnographies of parliament: culture and uncertainty in shallow democracies. Issue 1 (3rd April 2018) - Crewe, Emma
Abstract : Purpose: The purpose of this paper is to consider the challenges, advantages and limits of ethnographical approaches to the study of parliament. Challenges in the study of political institutions emerge because they can be fast-changing, difficult to gain access to, have starkly contrasting public and private faces and, in the case of national parliaments, are intimately connected to rest of the nation. Design/methodology/approach: Ethnography usually tends to be difficult to plan in advance, but especially so when parliament is the focus. Findings: Research in parliament requires clear questions but an emergent approach for answering them – working out your assumptions, deciding on the most appropriate methods depending on what wish to find out, and continually reviewing progress. Its great strengths are flexibility, ability to encompass wider historical and cultural practices into the study, getting under the surface and achieving philosophical rigour. Rigour is partly achieved through reflexivity. Research limitations/implications: One implication of this is that not only will each study of parliament be different, because each is embedded in different histories, cultures, and politics, but the study of the same parliament will contain variations if a team is involved. Originality/value: Ethnographical research is a social and political process of relating; interpreting texts, events and conversations; and representing the "other" as seen by observers.